Pengaruh Locus Of Control terhadap Budgetary Slack dengan Skill Teknologi sebagai Variabel Moderating pada Perumda Panglungan Kabupaten Jombang - Maulana Badar, Muhammad Rafli; Sundari, Siti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the effect of locus of control on budgetary slack with technological skill as moderation. The population in this study were employees of PERUMDA Panglungan Jombang Regency. Sample withdrawal using purposive sampling technique. This research uses a quantitative approach with Partial Least Square (PLS) analysis techniques The sample of this study was 120 respondents consisting of permanent employees and daily employees involved in the process. Based on the results obtained from this study, it shows that the locus of control variable has an effect on the budget gap. In the presence of technological skill as a moderating variable, locus of control has a positive and significant effect on budget constraints. The technological skills possessed by employees can reduce the budget constraints that occur due to an increase in locus of control of employees.